2008
DOI: 10.1016/j.clinthera.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of antibiotic prescribing in veterans with community-acquired pneumonia, sinusitis, or acute exacerbations of chronic bronchitis: A cross-sectional study

Abstract: Background-Previous studies evaluating antibiotic appropriateness in bacterial respiratory tract infections have focused only antibiotic choice and ignored other important aspects of prescribing such as dosing, drug-drug interactions, and duration of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Other studies in China have shown that antibiotic prescribing and use was connected with the interaction between physicians and patients [15,19]. A study in Pakistan and other studies have also demonstrated irrational prescribing of injections and antibiotics [3,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies in China have shown that antibiotic prescribing and use was connected with the interaction between physicians and patients [15,19]. A study in Pakistan and other studies have also demonstrated irrational prescribing of injections and antibiotics [3,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Appropriateness was measured using the Medication Appropriateness Index (MAI) [ 12 ]. The MAI is a validated tool that assesses the appropriateness of 10 different areas of medication prescribing: indication, effectiveness, dosage (based on indication and renal function), directions, practicality, drug–drug interactions, drug–disease interactions, duplication, duration, and expense [ 13 , 14 ]. For every prescribed medication, the reviewers answered each of the 10 questions in the MAI with either A (appropriate), B (not clearly appropriate), or C (inappropriate).…”
Section: Methodsmentioning
confidence: 99%
“…Another matter of concern is of prescribed antibiotic [26][27][28][29]. This has serious consequences: exposing the patients to adverse effects, increase of number of visits for mild issues [14,26,30], and development of resistant bacterium strains [14,31].…”
Section: Introductionmentioning
confidence: 99%